2003
DOI: 10.1021/cm020234c
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Phase Transition and Molecular Realignment of Glass-Forming Liquid Crystals Containing Cholesterol/Azobenzene Dimesogenic Compounds

Abstract: We synthesized dimesogenic liquid crystals with both cholesterol and azobenzene groups by esterification of 10,12-docosadiynedioic acid or docosanedioic acid with 4-alkyl-4′hydroxyazobenzene (or 4-hydroxyazobenzene) and cholesterol and studied the thermal, optical, and glass-forming properties. Especially, we focused on the effect of the length of the alkyl chain substituted on the azobenzene unit and the photochemical isomerization of the azobenzene unit on the properties of the mesophases of the compounds or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 59 publications
1
58
0
Order By: Relevance
“…The images of the LC textures were recorded using a close-up lens and a Sony DXC-950 CCD video camera system. Photoimaging was performed using a laser-scanning instrument, as previously reported [40]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The images of the LC textures were recorded using a close-up lens and a Sony DXC-950 CCD video camera system. Photoimaging was performed using a laser-scanning instrument, as previously reported [40]. …”
Section: Methodsmentioning
confidence: 99%
“…[4,40] Figure 7 displays the photoinduced shifts (325 nm, He-Cd laser) of CD8 doped with 3 wt.-% of polymers after UV irradiation. The reflection band shifted to shorter wavelengths upon increasing the irradiation energy and was accompanied by a decrease in the absorption at 360 nm arising from cis-trans isomerization (Fig.…”
Section: Effect Of Photoisomerizationmentioning
confidence: 99%
“…The correlative methods can be found in patents and research publications. [6][7][8][9][10][11] Glassy cholesteric liquid crystals possess the properties of conventional cholesteric liquid crystals and glassy thermoplastics. By preventing the crystallization of glassy cholesteric liquid crystals, rapid cooling is a very easy way of keeping the molecular helices.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier studies on similar host±guest systems containing various dopants, including dialkyl-and dialkoxy-substituted azobenzene, azoxybenzene, and biphenyl, have shown that the guest molecules play a crucial role in inducing the formation of smectic domains or clusters within the cholesteric molecular arrangement of the host. [12,24,30] These domains are understood to be consequences of order parameter fluctuations of cholesteric regions to and from a smectic-like arrangement, which are also termed as cybotactic groups. [31,33,34] XRD patterns of unaligned samples of BCn-CD8 mixtures exhibited two diffraction peaks, at 3.15 and 17.1 corresponding to layer spacing of 28.01 and 5.18 .…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
“…[7,8,23] We have recently demonstrated the use of cholesteric glassy liquid crystals as efficient materials for rewritable full-color imaging, based on thermal and photon mode. [19,20,24] Several mechanisms have been proposed to explain the role of dopant molecules in the modulation of macroscopic chirality of CLCs. Broadly these include: i) transfer of chirality from a chiral dopant to a mesogenic host, where the potential of the dopant is characterized by its helical twisting power (HTP), [17,25±29] ii) the impurity effect, where an achiral solute in a CLC medium perturbs the phase-transition temperatures of the host CLC leading to an isothermal modification of the helical pitch, and iii) a dopant-induced formation of smectic domains (smectic cybotactic groups) of the host CLC within its helical superstructure.…”
Section: Introductionmentioning
confidence: 99%